Kazimierz Goebel (1940-2022) - Prus, Stanisław (Topological Methods in Nonlinear Analysis, 2024)
On the 21st of July, 2022, a remarkable mathematician and a former rector of the Maria Curie-Skłodowska University in Lublin (UMCS) – prof. Kazimierz Goebel left us